'I Was Surprised to See You in a Chinese School': Researching Multilingually Opportunities and Challenges in Community-Based Research. (8th October 2019) - Ganassin, Sara; Holmes, Prue
Abstract: Researchers working in multilingual contexts must draw on their own linguistic resources when conceptualizing, planning, conducting, and reporting their studies, whether for theses or publications, or in dissemination to other stakeholders. However, these multilingual processes have received little attention in previous research. Drawing on an ethnographic study undertaken by Sara Ganassin in Chinese community language education, we investigate what opportunities and challenges a 'researching multilingually' perspective offers the researcher. We analyse narrative data and ethnographic observations to illustrate how the researcher drew on her multilingual resources vis-a-vis the linguistic spaces of her research context, the reflexive aspects of her multilingual positionality, and the ethical choices faced by her. From these insights, we make a theoretical and methodological case for embedding a researching multilingually approach in research that recognizes the linguistic resources of the researcher. The study has implications for building researcher capacity in multilingual research contexts, and for highlighting multilingual researcher processes that improve understanding, reporting, and representation of people from diverse linguistic and cultural horizons.